2004
DOI: 10.1007/bf02979632
|View full text |Cite
|
Sign up to set email alerts
|

The identification of readily bioavailable pollutants in lake shkodra/skadar using semipermeable membrane devices (SPMDs), bioassays and chemical analysis

Abstract: The combination of SPMD-based sampling with appropriate bioassays and chemical analysis provided an effective tool for the identification of environmentally relevant waterborne pollutants in Lake Shkodra/Skadar. Our results show that toxicologically relevant HOPs including EROD-inducing and potentially estrogenic compounds are widely distributed in the lake and readily available for uptake by aquatic biota. Our results also suggest that alkylated PAHs rather than parent compounds may be of greater toxicologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(29 citation statements)
references
References 34 publications
0
29
0
Order By: Relevance
“…Similar phenomenon also occurred in other environmental matrix, for example, Muusse et al (2012) found PAH can only explain up to 9% of the AhR agonist activity in roadside snow samples in Norway. Rastall et al (2004) reported that TEQ PAH were 3 to 4 orders of magnitude lower than the respective TEQ bio in their SPMD samples from a lake in the Balkans. Our recent publication also reported that TEQ cal were 2-10% of TEQ bio in a drinking water reservoir (Wang et al, 2014b).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Similar phenomenon also occurred in other environmental matrix, for example, Muusse et al (2012) found PAH can only explain up to 9% of the AhR agonist activity in roadside snow samples in Norway. Rastall et al (2004) reported that TEQ PAH were 3 to 4 orders of magnitude lower than the respective TEQ bio in their SPMD samples from a lake in the Balkans. Our recent publication also reported that TEQ cal were 2-10% of TEQ bio in a drinking water reservoir (Wang et al, 2014b).…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, this device is also referred to as virtual organism (VO) which provides an integrative sampling method for a wide array of bioavailable waterborne HOCs (Schramm et al, 2013). The VO followed by the combination of chemical and biological analyses has been proven to be a resource efficient tool for the exposure assessment of environmentally relevant water borne pollutants in drinking water resources (Rastall et al, 2004;Wang et al, 2014b).…”
Section: Introductionmentioning
confidence: 99%
“…Similar phenomenon also occurred in other environmental matrix, for example, Muusse et al (2012) found PAH can only explain up to 9% of the AhR agonist activity in roadside snow samples in Norway. Rastall et al (2004) reported that TEQ PAH were 3-4 orders of magnitude lower than the respective TEQ bio in their SPMD samples from a lake in the Balkans. Due to the complex nature of environmental samples together with limited instrumental support, causative agents of observed bioassay reports are often not identified.…”
Section: Teq Bio From Erod Assay and Mass Balance Analysis Between Tementioning
confidence: 97%
“…The combination of the EROD bioassay with chemical analysis has been largely used to evaluate the AhR activity in sediment and soil (Kinani et al, 2010;Shen et al, 2008;Qiao et al, 2006;Hong et al, 2012), and effluents of wastewater treatment plants (Dagnino et al, 2010;Ma et al, 2005;Reungoat et al, 2010). But few references could be available on evaluating AhR activity in surface water (Rastall et al, 2004). Risk assessment for dioxin-like compounds in surface water or drinking water resources is difficult mainly because these compounds are usually low in concentrations, as well as the effects of many endpoints, typically falling below the detection limit.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation